2004
DOI: 10.1016/j.femsle.2004.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-free NisI: interaction with nisin and contribution to nisin immunity via secretion

Abstract: Nisin-producing Lactococcus lactis cells protect their own cytoplasmic membrane by specific immunity proteins, NisF/E/G and NisI, a transporter complex and a lipoprotein, respectively. A portion of NisI is secreted to the medium in a lipid-free form (LF-NisI). Here, kinetics of the interaction between nisin and LF-NisI was examined by surface plasmon resonance analysis. The affinity constant K D for the interaction was calculated to be in the micromolar range. Contribution of the secreted LF-NisI to nisin immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
(32 reference statements)
2
25
0
Order By: Relevance
“…Nisin Binding-Previously it was shown by native PAGE that NisI directly binds to nisin (24) although the interaction is rather weak with a K D for the interaction in the micromolar range (25). Stein et al (24) also showed that NisI does not bind the structurally closely related subtilin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nisin Binding-Previously it was shown by native PAGE that NisI directly binds to nisin (24) although the interaction is rather weak with a K D for the interaction in the micromolar range (25). Stein et al (24) also showed that NisI does not bind the structurally closely related subtilin.…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown by native PAGE that in vitro NisI specifically binds to nisin but not subtilin (24). A nisin binding affinity in the low micromolar range was determined for lipid-free NisI by surface plasmon resonance (25). Furthermore, experiments with C-terminal truncation variants of NisI suggested that the C-terminal 22 amino acids of NisI are involved in nisin immunity (26,27).…”
mentioning
confidence: 99%
“…The equilibrium dissociation constant (1.2 M) for the binding interaction between HalI and HalC8 evaluated by the SPR assay was similar to that for the NisInisin interaction (range, 0.6 to 2 M) (30). The moderately strong binding may be helpful for releasing the captured peptide antibiotic into the environment again by some unknown mechanism.…”
Section: Discussionmentioning
confidence: 56%
“…When lantibiotics are considered, nisin A is the only one that has been subjected to a considerable amount of research concerning resistance (13,14,15,22,23,(29)(30)(31). Very little is known about resistance to other lantibiotics, such as gallidermin, although work has been done to show how resistance works in the producer strain of the antibiotic (17).…”
Section: Discussionmentioning
confidence: 99%